FINANCIAL FEASIBILITY ANALYSIS OF OYSTER MUSHROOM CULTIVATION BASED ON SAWDUST - Futri, Srie Nurmala; Salampessy, Messalina Lovenia; Lidiawati, Ina (Forestry Study Program University Of Mataram, 2025)
The sawmill industry produces sawdust waste that is still not utilized optimally. Currently, the processing of wood waste in the form of sawdust is still carried out in an inappropriate way such as disposal into rivers and incineration, even though the waste has the potential to be used in various products of economic value such as oyster mushroom planting media. For this reason, the purpose of this study is to find out the percentage of sawdust waste that can be used and analyze the level of financial feasibility of developing an oyster mushroom cultivation business. The data collection methods used are observation, interviews, and documentation with data analysis using percentage analysis and economic feasibility analysis using NPV, IRR, BCR, Payback Period, and sensitivity analysis criteria. The results showed that the percentage of sawdust waste utilization reached 89.60% (3,000 kg) of the total production, with details of 44.80% (1,500 kg) for oyster mushroom planting media, 29.90% (1,000 kg) for cowshed floor mats, and 14.90% (500 kg) for fertilizer. The analysis of the financial feasibility of the business is considered feasible to be developed, with an NPV of IDR 43,336,430, IRR of 49.6654%, BCR of 2.64, and a Payback Period of 2 years and 20 days. For this reason, efforts to utilize sawdust waste need to be increased.